Bazedoxifene Plays a Protective Role against Inflammatory Injury of Endothelial Cells by Targeting CD40. (15th December 2020) - Song, Wenmin; Lv, Yu; Tang, Zizhao; Nie, Fangqin; Huang, Panhao; Pei, Qi; Guo, Ren
Abstract : The inflammatory response and oxidative stress play key roles in the formation and development of atherosclerosis. Bazedoxifene is a new IL6/GP130 inhibitor recommended by the FDA for clinical use as a selective estrogen receptor modulator. However, its role in cardiovascular diseases has been poorly studied. In our study, we explored the mechanism of bazedoxifene's protective effect against inflammatory injury of vascular endothelial cells (VECs) stimulated by TNF- α . Various methods were used to verify the effect of bazedoxifene on VECs, including a cell viability assay, a wound healing assay, immunofluorescence staining, and western blotting. Our results showed that TNF- α could induce inflammatory damage to VECs, which manifested as upregulated expression of CD40, increased production of ROS, enhanced adhesion of THP-1 cells to VECs, and impaired viability and migration of VECs, while bazedoxifene could significantly reduce the endothelial damage caused by TNF- α . In addition, we found that an siRNA targeting CD40 dramatically alleviated the VEC damage induced by TNF- α . Therefore, we explored the potential relationship between bazedoxifene and CD40. Our data suggest that bazedoxifene has a protective effect against VEC damage induced by TNF- α and that its underlying mechanism may be related to the regulation of CD40.